Effects of an outdoor horticultural activities program on cognitive and behavioral functioning, mood, and perceived quality of life in people with dementia: a pilot study - Borella, Erika; Melendugno, Andrea; Meneghetti, Chiara; Murroni, Veronica; Carbone, Elena; Goldin, Giulia; Cavalli, Raffaele; Basso, Andrea; Pazzaglia, Francesca (Frontiers in Psychology, 2023)
Introduction: One of various non-pharmacological treatments for people with dementia (PwD) is horticultural therapy. The aim of this double-blind, pre- and post-test, pilot study was to examine the effects of horticultural activities (HA) for PwD at a residential and daytime care facility. Whether combining HA with elements drawn from other psychosocial interventions (cognitive stimulation) would maximize any benefits was also newly examined. Materials and methods: Twenty-four PwD were involved either in HA, alone (TG1, N=7) or combined with some cognitive stimulation (TG2, N=8), or in indoor treatment-as-usual activities (CG, N=9). Benefits were assessed in terms of general cognitive functioning (for participants with mild-to-moderate dementia), mood, behavioral and psychological symptoms, and quality of life. Results: No differences emerged between TG1 and TG2 in any outcome measure, so the two groups were combined (N=15). Compared with the CG, the TG involved in HA exhibited less frequent and severe behavioral and psychological symptoms, and an improved mood after the intervention. Caregivers also reported less distress in the TG after the intervention than in the CG. Considering only PwD with mild-to-moderate dementia, the TG also showed benefits in a measure of general cognitive functioning, and self-reported quality of life, compared with the CG. Discussion: Our results further confirm that engaging PwD in participatory HA in contact with natural elements can improve their dementia symptoms and quality of life, and their caregivers’ distress. Our findings also suggest the need to consider dementia severity when assessing the benefits of horticultural therapy.